Euro Area : Staff Report on the Monetary and Exchange Rate Policies of the Euro Area; Supplement Updating Information on Recent Economic Developments and Policies in the Euro Area; Supplement on EU Trade Policies; Public Information Notice Following Consultation; Two Statements by Representative on the IMF Executive Board for France, on Behalf of Euro-Area and EU Members. (IMF Staff Country Reports; Country Report, 2000)
For the time being-and possibly for a considerable time to come-developments and prospects for the euro area are quite favorable. This upbeat outlook is underpinned by buoyant activity indicators and a supportive policy mix. High household and business confidence, rising capacity utilization and industrial production, strong job creation, and-so far-employment-friendly wage settlements point to sustained activity in the near term. Moreover, the macroeconomic fundamentals in the euro area appear much sounder than in previous recoveries.